The influence of the project team efficacy and organizational factors on the success of mining project management - Saenz Arteaga, Arturo Rodolfo (2020)
Some authors have proposed that project team efficacy influences the success of project management; however, this relationship has not been well investigated. The objectives of this study are to analyze the relationship between project team efficacy and the success of project management and to examine three moderator variables (task uncertainty, task interdependence, and chaos effect) in the relationship between them. This study was based on a sample of 52 mining work teams. The suggested hypotheses were con-firmed, there is an influential relationship between project team efficacy and the success of mining project management, as well as the significance of the moderate variables.